2015
DOI: 10.3989/scimar.04093.25a
|View full text |Cite
|
Sign up to set email alerts
|

Topographical variation in lipid content and morphological structure of the blubber in the striped dolphin

Abstract: Summary:We investigate stratification patterns and topographical variations in the blubber of the striped dolphin (Stenella coeruleoalba) to gain insights into its regionally-specific functions. We collected blubber from 10 stranded striped dolphins (5 females and 5 males) from the eastern coast of Spain in 2007-2009, at 11 body positions. Histological measurements (adipocyte number and area) and blubber lipid content were analysed for each position. Histological measurements revealed stratification of blubber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 49 publications
3
20
0
Order By: Relevance
“…Various other studies have also shown that blubber thickness was a poor index of nutritive condition, as it was not correlated with changes in overall body fat reserves (Aguilar et al, 2007;Caon, Fialho, & Danilewicz, 2007;Evans et al, 2003;Gómez-Campos et al, 2015;Koopman, 2007;Read, 1990;Ruchonnet et al, 2006). It is well recognized across all species that blubber, in addition to its role as a deposit of energy, serves important functions as an insulator, it is involved in active thermoregulation, it streamlines the body, facilitates hydrodynamic locomotion, contributes to water balance, and provides buoyancy (Iverson, 2009).…”
Section: Lipid Content Variation As An Indicator Of Body Condition:mentioning
confidence: 98%
See 1 more Smart Citation
“…Various other studies have also shown that blubber thickness was a poor index of nutritive condition, as it was not correlated with changes in overall body fat reserves (Aguilar et al, 2007;Caon, Fialho, & Danilewicz, 2007;Evans et al, 2003;Gómez-Campos et al, 2015;Koopman, 2007;Read, 1990;Ruchonnet et al, 2006). It is well recognized across all species that blubber, in addition to its role as a deposit of energy, serves important functions as an insulator, it is involved in active thermoregulation, it streamlines the body, facilitates hydrodynamic locomotion, contributes to water balance, and provides buoyancy (Iverson, 2009).…”
Section: Lipid Content Variation As An Indicator Of Body Condition:mentioning
confidence: 98%
“…The posterior dorsal area of mysticetes is a major site for lipid storage in both the blubber and the muscle (Lockyer et al, 1985), but this may not be the case for beaked whales, particularly if they are more similar to small odontocetes. In small odontocetes, the blubber in the thoracic-abdominal region is hypothesized to play an important role in insulation and energy storage, whereas the region posterior to the dorsal fin is thought to primarily act to maintain hydrodynamic and locomotory functions and is metabolically inert (Gómez-Campos, Borrell, Correas, & Aguilar, 2015;Koopman, 1998;Koopman et al, 2002;Tornero, Borrell, Forcada, Pubill, & Aguilar, 2004).…”
Section: Lipid Content Variation As An Indicator Of Body Condition:mentioning
confidence: 99%
“…The reason why the dorsal area also presented higher hormone levels measured as ng cortisol/g lipid is unclear. In striped dolphins, the dorsal area presents the lower adipocyte number and lipid content compared to the ventral locations (Gómez‐Campos et al, 2015), further hindering interpretation. Blubber has been recognized as a site of active steroid metabolism (Galligan et al, 2018) and evidence in other mammals suggests that the hormonal activity of the adipose tissue differs across body regions (Lindsay et al, 2003).…”
Section: Id Sex Cause Of Death Body Conditionamentioning
confidence: 99%
“…The blubber is the lipid-rich hypodermis that has different biological functions, such as the storage of energy, thermoregulation, buoyancy control and hydrodynamic streamlining (Pabst et al, 1999). Moreover, the blubber of marine mammals is a heterogeneous tissue composed of layers or strata (inner, middle and outer) that play different roles and exhibit different biochemical compositions (Evans et al, 2004;Struntz et al, 2004;Gómez-Campos et al, 2015). The inner and middle layers are mainly devoted to fat mobilisation and the lipid content greatly fluctuates depending on the reproductive and migratory cycle of individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Fat deposition mainly occurs in the outer layer, which is considered metabolically more inert and has the primary function of thermal insulation. The outer layer is also little affected by changes in nutritive conditions (Aguilar and Borrell, 1991;Gómez-Campos et al, 2015). Moreover, blubber accumulates high concentrations of persistent organic pollutants (POPs), since organochlorine compounds are highly apolar compounds and dissolve in neutral lipids.…”
Section: Introductionmentioning
confidence: 99%